A comparison of debt measures in fiscal statistics and public sector financial statements. Issue 7 (10th November 2018) - Dabbicco, Giovanna
Abstract : This paper examines the differences between measures of debt used to analyse a government's financial position. It compares the statistical and accounting approaches and presents a way of reconciling the two statements: thereby identifying possible convergence between GPFS and GFS. In doing so, it contributes to the ongoing international debate on harmonization of public sector accounting standards, such as IPSAS/EPSAS and GFS.